The Relationship Between Career Social Support and Employability of College Students: A Moderated Mediation Model - Xia, Tiansheng; Gu, Honglei; Huang, Yamei; Zhu, Qian; Cheng, Yufang (Frontiers in Psychology, 2020)
This study examines the underlying mechanism that connects career social support with employability among a sample of 392 Chinese college students. The results showed that career social support had a positive effect on career adaptation and employability of college students, and career adaptation mediated the relationship between career social support and employability. Furthermore, proactive personality was found to play a moderating role in linking career adaptation and employability. Specifically, high levels of proactive personality strengthen the enhancing effect of career adaptation on the employability of college students. Therefore, there was a moderated mediation effect between career social support and employability of college students.